Metal (Fe, Co, Ce or La) doped nickel catalyst supported on ZrO2 modified mesoporous clays for CO and CO2 methanation. (1st November 2016) - Lu, Huailiang; Yang, Xuzhuang; Gao, Guanjun; Wang, Jie; Han, Chenhui; Liang, Xiaoyuan; Li, Changfu; Li, Yuanyuan; Zhang, Weida; Chen, Xuetao
Graphical abstract: Highlights: Ni-M (La, Ce, Fe or Co)/ZrO2 -clays show excellent catalytic activity for CO and CO2 methanation. La, Ce, Fe or Co promotes NiO dispersion and enhance the thermal stability of catalyst. Cerium doped catalyst shows superior catalytic activity to other elements for CO methantion. Ion doped catalyst shows superior catalytic activity to other elements for CO2 methantion. High performance is resulted from synergy of doped element, ZrO2 modified clays and nickel species. Abstract: The metal (La, Ce, Fe or Co) doped nickel catalysts supported on zirconia modified clays have been prepared by the incipient wetness impregnation method. The zirconia modified clays have a new mesoporous structure with zirconia nanoparticles highly dispersed on the partly damaged clay layers and have been prepared in one pot by the hydrothermal treatment. The catalytic performances of the catalysts for CO and CO2 methanation have been investigated. The catalysts have been characterized by X-ray diffraction (XRD), transmittance electron microscopy (TEM), H2 temperature-programmed reduction (H2 -TPR), nitrogen adsorption-desorption, and thermogravimetry and differential thermal analysis (TG-DTA). It is found that small amount of La, Ce, Co or Fe in the nickel catalyst supported on the zirconia modified clays promote the dispersion of NiO nanoparticles, increase the quantity of the reduced active nickel species in the catalyst and enhance the thermal stability for CO and CO2 methanation. The addition of La or Ce in the catalysts is beneficial to CO methanation, and Ce is superior to the other three elements for this reaction. The addition of Fe and Co is beneficial to CO2 methanation, and Fe is superior to the other three elements for CO2 methanation. The metal doped catalysts exhibit excellent stability for both CO and CO2 methanation. The outstanding catalytic performance of the catalyst is resulted from the synergistic effect of doped metal, zirconia on the clay layers, the mesopores on support, as well as the active nickel species.